Utilização de armadilha de emersão para captura de flebotomíneos em área com transmissão e sem transmissão de LVA e LTA, na região centro-oeste do estado de São Paulo, Brasil - Silva, Denise Theodoro da [UNESP] (2013)
Currently, vector-borne diseases are a major public health problems. In last 20 years, many of these diseases have reappeared or spread to new parts of the planet, as leishmaniasis, which is transmitted by several species of sandflies. Systematic monitoring of the soil surface combined with emergence traps must identify sandflies natural breedings sites and studies of their larval biology, help to develop possible measures for vector control at this stage, since there is difficulty in to control adult sandfly. Accordingly , this study aimed to identify areas of greatest risk for the development and maintenance of sandflies based on environmental characteristics, to catch sandflies by an adapted emergence trap and analytical results of soil in urban environment . A total of 333 traps were placed in 2 municipalities from November 2012 to January 2014. Was possible to observe 11,857 insects, of which 9,239 belonged to the Order Diptera. However, no sandfly medical and veterinary importance was captured. Soil analysis revealed that the soil from the study area is characterized as sandy, with low acidity and high content of organic matter. The presence of animals like dog, cat, chicken, cattle and horses, as well as fruitful as both ornamental vegetation, were noted in backyards. Unable to perform the correlation between environmental characteristics , soil and presence of natural breeding sites of sandflies by not having captured no copy in both municipalities . However, other studies should be conducted, because this type of information is important for the planning and development of control measures for the vector, since the measures directed to reservoir (dog) , are not well accepted by population